Characterization and functionality of carob germ proteins - Smith, Brennan M. (Kansas State University, 2009)
The biochemical, physical and baking properties of caroubin, the main protein in the carob bean, were characterized. The biochemical properties of caroubin were analyzed using reversed-phase high performance liquid chromatography (RP-HPLC), size exclusion chromatography coupled with multi-angle laser light scattering (SEC-MALS) and micro-fluidics analysis. The physical and baking properties of caroubin were characterized via SE-HPLC, laser scanning confocal microscopy, farinograph mixing, and texture profile analyzer analysis. Using a modified Osborne fractionation method, carob germ flour proteins were found to contain ~32% albumin and globulin and ~68% glutelin with no prolamins detected. When divided into soluble and insoluble protein fractions under non reducing conditions it was found that caroubin contained (~95%) soluble proteins and only (~5%) insoluble proteins. As in wheat, SEC-MALS analysis showed that the insoluble proteins had a greater Mw than the soluble proteins and ranged up to 8x107 Da. These polymeric proteins appeared to play a critical role in protein network formation. Analysis of the physical properties of carob germ protein-maize starch dough showed that the dough’s functionality was dependent on disulfide bonded protein networks, similar to what is found in wheat gluten. When baked into a bread these proteins were shown to have a possible improving affect by decreasing staling in gluten-free breads. This was evident when compared to a gluten-free batter bread, and a wheat bread over a five day period.
Keywords: Carob; Carob germ; gluten; gluten-free; celiac; Agriculture, Food Science and Technology (0359)